2006
DOI: 10.1167/iovs.05-1518
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α, but Not Latanoprost, Increases the Ca2+Sensitivity of the Pig Iris Sphincter Muscle

Abstract: PGF(2)alpha, but not latanoprost, induced Ca(2+) sensitization of the pig iris sphincter muscle in an MLC phosphorylation-dependent manner through the rho-rho kinase pathway. The effect of latanoprost on the Ca(2+) sensitization mechanism was different from that of PGF(2)alpha and was thought to play a beneficial role in glaucoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…Prostaglandin F 2␣ , but not latanoprost, was found to increase the Ca 2ϩ sensitivity of the pig iris sphincter muscle in an MLC phosphorylation-dependent manner. 35 The lack of apparent effect of latanoprost on MLC phosphorylation in HTFs in the present study suggests that MLC phosphorylation-independent Ca 2ϩ sensitization may underlie the latanoprost-induced contraction of these cells. However, we found that ML-7 (a selective inhibitor of MLC kinase) prevented HTF-mediated collagen gel contraction regardless of the absence or presence of latanoprost, suggesting that MLC phosphorylation is necessary for both basal and stimulated HTF contraction.…”
Section: Iovsmentioning
confidence: 45%
“…Prostaglandin F 2␣ , but not latanoprost, was found to increase the Ca 2ϩ sensitivity of the pig iris sphincter muscle in an MLC phosphorylation-dependent manner. 35 The lack of apparent effect of latanoprost on MLC phosphorylation in HTFs in the present study suggests that MLC phosphorylation-independent Ca 2ϩ sensitization may underlie the latanoprost-induced contraction of these cells. However, we found that ML-7 (a selective inhibitor of MLC kinase) prevented HTF-mediated collagen gel contraction regardless of the absence or presence of latanoprost, suggesting that MLC phosphorylation is necessary for both basal and stimulated HTF contraction.…”
Section: Iovsmentioning
confidence: 45%
“…This corresponds to the low bimatoprost conversion rates observed in isolated bovine and human ocular tissues ( Maxey et al , 2002 ; Davies et al , 2003 ; Krauss and Woodward, 2004 ). Even the ester latanoprost undergoes low enzymatic hydrolysis in certain tissues, as indicated by the very weak activity of latanoprost in the isolated feline ( Resul et al , 1997 ) or porcine iris ( Hasegawa et al , 2006 ). Finally, potent stimulation of the isolated rabbit uterus was attributed to the activity of intact bimatoprost, since bioassay indicated no enzymatic hydrolysis to the free acid metabolite ( Chen et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…5−7,17,21 Hasegawa et al 17 reported that, in isolated α-toxin-permeabilized pig iris sphincter muscle, Y27632, a Rho-kinase inhibitor, inhibited the carbachol-induced enhancement of contraction at a fixed concentration of intracellular free Ca 2+ [Ca 2+ ] i . Carbachol stimulates the M3 muscarinic receptor coupled to a heterotrimetric GTPbinding protein (Gq).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings suggest that PKC is not involved in the generation of spontaneous tone in the resting phase. Hasegawa et al 17 observed that, in the α-toxin-permeabilized pig iris sphincter muscle, Gq-coupled receptor-mediated Ca 2+ sensitization was inhibited by Y27632 but not by GF109203X. Furthermore, they also observed that PDBu, an activator of PKC, had no effect on the resting tension in the intact and α-toxin-permeabilized pig iris sphincter muscle and that CPI-17 expression was under detectable levels by immunoblot analysis in this tissue.…”
Section: Rho-kinase Is Involved In Spontaneous Tonementioning
confidence: 94%
See 1 more Smart Citation